Using camera settings templates ("Scene Modes") for image scene classification of photographs taken on manual/expert settings - Ku, W. (2013)
Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)